Signaling or insider opportunism: an investigation of repurchase activity in Vietnam - Ly Thi Hai Tran; Thao Thi Phuong Hoang (Cogent Economics & Finance, 2022)
This paper examines whether share repurchase announcements are signals of undervaluation or insiders' opportunistic activities by investigating insider trading patterns surrounding buyback announcements in Vietnam. Consistent with the insider opportunism hypothesis, we show that insiders are net buyers before the announcements but they sell intensively after the event. We also find that repurchase announcements with subsequent net insider selling are not followed by an improvement in firms' operating performance but associated with underperformance in long-term stock returns. Overall, our findings suggest that a proportion of repurchase announcements in Vietnam are subject to insider opportunism; therefore, short-swing rules should be regulated to limit insider opportunistically trading around repurchase announcements.
Keywords: 330; share repurchase; insider trading; signaling hypothesis; insider opportunism; managerial opportunism; Vietnam